Drivers of Socially Responsible Investments Across Europe - Janina Rochell; Thomas Cauthorn; André Höck; Bernhard Zwergel (Credit and Capital Markets – Kredit und Kapital, 2020)
The European Union wants to foster the sustainable growth of the economy by using the financial markets as an intermediary. Thus, politicians need to know which factors account for differences in socially responsible investments (SRI) between countries to create an efficient framework, which supports SRI across Europe. This study aims to provide important insights about the drivers of SRI markets for politicians as well as academics. To the best of our knowledge, this is the first study that provides quantitative evidence on the framework established by Scholtens/Sievänen (2013) using a comparatively large data sample comprising 13 European countries during a period from 2005 to 2015. Our results can be summarized as follows: Firstly, we show that economic wealth and the size of the pension market of a country influence the size of the SRI market per capita. In particular, it seems that countries need a certain level of wealth and pension market size to start adopting basic sustainability strategies like negative screening. Secondly, we provide evidence that the differences in national SRI evolvement stem from the individual cultural characteristics of a nation. For example, masculinity, as seen by the revenue orientation of a country, prevents the emergence of more advanced SRI strategies, like engagement or integration. However, femininity, which relates to a more societal and environmental orientation, drives the emergence of more advanced SRI strategies. In this context, the recommendation to European policymakers is to opt for a minimum standard for the integration of more advanced SRI strategies, so that non-feminine countries also implement a deep-rooted sustainable investment behavior.
Keywords: A13; G11; G15; M14; 330; Socially Responsible Investment; Economic Growth; Financial Markets; Institutional Systems; Culture